Effects of broiler breeder genetic, diet type, and feeding program on maternal antibody transfer and development of lymphoid tissues in chicken progeny - Leandro, N. M.; Ali, R.; Koci, M.; Moraes, V. [UNESP]; Malheiros, R. D.; Wineland, M. J.; Oviedo-Rondon, E. O. (Poultry Science Assoc Inc, 2011)
Maternal antibody (MatAb) transfer is important for early chicken survivability. Diet composition and the amount of feed given to breeder pullets during rearing may affect the development of immunity and the transfer of MatAb to progeny, and could affect progeny performance and resistance to disease. The effects of broiler breeder nutrition and feeding management practices were evaluated for the transfer of MatAb to progeny and for spleen and bursa development at hatching in 2 genetic strains (A and B). In this experiment, the levels of MatAb against Newcastle disease virus were assessed by enzyme-linked immunosorbent assays in serum samples taken of pedigreed chicken progeny from hatching to 13 d of age. Chickens were fed corn-and wheat-based diets, as were their parents. The breeder feeding program and diet type altered the Newcastle disease virus MatAb found in progeny at hatching and affected how long these antibodies were maintained in circulation. Bursal follicle size at hatching was influenced by an interaction among all factors evaluated. Percentage of white pulp in the spleen was affected mainly by genetic strain and diet type, but responses varied according to the breeder feeding program. It was concluded that breeder feeding programs influence MatAb transfer and half-life, and may also affect the early development of lymphoid tissues.
Keywords: breeder; bursa; feeding program; genetics; immunity; maternal antibody; spleen